Impact of corn straw and straw-derived biochar returning to the field on soil carbon fractions, carbon-converting enzyme activities, and cbbL bacterial community structure - Li, Jiawang; Ren, Qina; Yu, Hang; Wu, Xiangyu; Yin, Yuan; Yue, Zhonghui; Bai, Xin (Frontiers in Microbiology, 2025)
IntroductionStraw return is recognized as an effective practice for improving soil organic matter. However, in the black soil regions of China, limited information is available on how the individual or combined application of crop straw and straw-derived biochar influences soil carbon-converting enzymes and the soil cbbL bacterial.MethodsThis study conducted three consecutive growing-season field experiments in a typical black-soil zone using a soybean–corn rotation system. Four straw return treatments were established based on equal carbon input (2,500 kg·hm-2), including the blank control with no carbon source (T0), corn straw applied alone (T1), straw-derived biochar applied alone (T2), and their co-application at ratios of 1:3 (T3) and 3:1 (T4).ResultsThe results indicated that compared to T0, the four treatments had no significant effect on soil labile organic carbon (LOC) but significantly effect soil organic carbon (OC), dissolved organic carbon (DOC), and microbial biomass carbon (MBC) (p < 0.05). Notably, soil carbon mineralization was significantly enhanced under T1 and T3, increasing by 13.38% and 13.28%, respectively. All the treatments significantly reduced the relative abundance of Alphaproteobacteria (dominant class) and Nitrobacter (dominant genus) in the cbbL bacterial community, and significantly promoted soil enzyme activities: SCL (cellulase), SAI (amylase) and SSC (sucrase) increased by 2.95–15.35%, 6.10–19.26% and 10.84–53.17%, respectively. Comprehensive analysis demonstrated that straw-derived biochar incorporation directly and significantly affected the cbbL bacterial community structure, while both straw and biochar significantly affected the enzyme activities. Enzyme activities directly influenced the levels of soil carbon fractions, which ultimately determined the soil organic carbon mineralization capacity.DiscussionOverall, the response of carbon mineralization to straw and biochar application was primarily driven by the content of soil carbon fractions, which were regulated by enzyme activity. This study provides a scientific basis for enhancing the carbon sequestration potential of black soils in China.